Configurations of masculinity : a feminist perspective on modern political theory - Di Stefano, Christine (Cornell paperbacks, 1991)
In this pathbreaking book, Christine Di Stefano offers a new perspective on the dimension of gender in modern political thought in order to elucidate what is specifically masculine in political theory. Attempting to clear some conceptual space for feminist political theory, Di Stefano provides innovative readings of Hobbes, Marx, and J. S. Mill.